Key Factors for the Successful Implementation of the National Innovation Policy: The Case of Lithuania - JUKNEVICIENE, Vita (Annals of Spiru Haret University. Economic Series, 2019)
Innovations play the crucial role in the economic growth in modern countries. It requires the technological progress and smart people as two main resources, needed for the actors in the national innovation system. Results of the national innovation system depend on the national innovation policy: its goals and priorities set in the agenda, policy formulation and adoption, its implementation process and its correction after the evaluation. But despite of the same stages of the public policy cycle, some countries implement the successful innovation policy (gain competitive advantage and the economic-social benefit from it) and some countries struggle (they try to catch-up other countries in the field of innovations). Lithuania as a small developed country in the EU has made a huge progress in terms of economics, social and technological advantage. However, despite of declared goals of innovation policy and the priorities in national strategies, governmental funding, promotion and support, the national progress in innovations in Lithuania still remains low. Therefore, stimulus and barriers for the successful implementation of Lithuanian innovation policy should be identified and analyzed, looking for problems and possible solutions. This paper aims to explain main theoretical implications about the successful implementation of innovation policy and to reveal how it is reflected in the case of national innovation policy in Lithuania. Scientific methods of the literature analysis, document analysis, secondary data analysis, summarizing, and interpretation are used in the research.